Adventure stories - King, Clive; Davidson, Andrew (Kingfisher London, 2004)
Action packed and full of drama, these 21 stories tell of daring deeds and fearless heroes. Across frozen mountain wastes and stormy seas, through steamy jungles and dusty savannahs, they battle against nature and their enemies.